KESESUAIAN PEMANFAATAN PERAIRAN BAGI PENGEMBANGAN PERIKANAN BUDIDAYA DI KAWASAN TELUK STARING KONAWE SELATAN - Abdul Rahman; Akhmad Mansyur (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
The aim of this research were to analyzed the suitability of the use space Staring bay in South Konawe district for the development of sustainable aquaculture. The research method was survey for primary data and secondary data. This study used spatial analysis approaches and determined the suitability of land used geographical information system. The research results showed two categories of waters suitability for development of sustainable aquaculture that is very appropriate category and appropriate category. Very appropriate category there is 570 Ha. And appropriate category there is 778 Ha. Both of this category can using as the base of phycoculture development, kerapu fish, with using Pent cage and Ploting cage. Beside that, it can use as the development for sea cucumber cultivation, and conservation area of lobster spawning habitat as a support for mariculture lobster seed at Staring bay. Itcan using too as the fisheries area of small pelagic and reef fish.Key words: Aprropriate Area, Fisheries Culture, Staring Bay